Esemtia, Comprehensive Platform To Meet Needs In A Teaching Context - et. al., Edwin Fernando Cárdenas Cárdenas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Esemtia digital platform is designed for communication between the organization, teachers, students and families to facilitate their roles in the teaching and learning process. It is used in educational institutions in several countries, but few studies have disseminated the results of its application. A study was conducted at the Colegio Técnico Salesiano Don Bosco, Quito, where it is applied with the hypothesis of good results. The research is descriptive, participatory, transversal, non-experimental, quantitative and qualitative. From the universe of the personnel who study and work at the school and parents, a random sample of volunteers was selected, organized in four groups: 524 students, 601 parents, 81 teachers and 8 administrative staff. Surveys were administered to find out their satisfaction with the use of this platform. The analysis and synthesis of the results showed high satisfaction rates and identified limitations.